Ada Twist, scientist - Beaty, Andrea; Roberts, David, 1970- (New York : Abrams Books for Young Readers, 2016)
Ada Twist is a very curious girl who shows perseverance by asking questions and performing experiments to find things out and understand the world.
Keywords: Curiosity -- Fiction; Scientists -- Fiction; Science -- Experiments -- Fiction; Perseverance (Ethics) -- Fiction; Stories in rhyme